AUTHENTIC ASSESSMENT IN INDONESIAN LANGUAGE LEARNING: A SYSTEMATIC LITERATURE REVIEW OF PEDAGOGICAL, TECHNOLOGICAL, AND SOCIOCULTURAL DIMENSIONS - Reni Nur Eriyani; Fathiaty Murtadho; Hestiyani Parai (Jurnal Bastra (Bahasa dan Sastra), 2026)
The growing emphasis on contextualized and learner-centered pedagogy has heightened interest in authentic assessment in language education. However, systematic reviews focusing specifically on Indonesian language learning remain scarce. This systematic review analyzes research on authentic assessment in language learning, with particular attention to its application in Indonesian language education contexts. Following PRISMA guidelines, we conducted a comprehensive search across Scopus, ERIC, and Google Scholar databases, identifying 10 empirical and conceptual studies published between 2015-2025. The TCCM (Theory, Context, Characteristics, Methodology) framework guided the analysis. Thematic synthesis revealed three major trajectories: (1) a pedagogical shift from summative to formative and authentic evaluation; (2) the transformative influence of digital technologies, including AI and mobile-assisted learning; and (3) the growing emphasis on sociocultural and intercultural dimensions. Authentic assessment functions not only as a measurement tool but also as a pedagogical process fostering metacognition, collaboration, and inclusivity. This review offers a novel integrative perspective linking authenticity, technology, and sociocultural context within an ecological framework. The findings highlight the need for culturally responsive and ethically grounded digital assessment practices in Indonesian language education.